Proteomic studies of the abiotic stresses response in model moss – Physcomitrella patens - Wang, Xiaoqin; Liu, Yanli; Yang, Pingfang (Frontiers in Plant Science, 2012)
Moss species Physcomitrella patens has been used as a model system in plant science for several years, because it has a short life cycle and is easy to be handled. With the completion of its genome sequencing, more and more proteomic analyses were conducted to study the mechanisms of P. patens abiotic stress resistance. It can be concluded from these studies that abiotic stresses could lead to the repression of photosynthesis and enhancement of respiration in P. patens, although different stresses could also result in specific responses. Comparative analysis showed that the responses to drought and salinity were very similar to that of abscisic acid, while the response to cold was quite different from these three. Based on previous studies, it is proposed that sub-proteomic studies on organelles or protein modifications, as well as functional characterization of those candidate proteins identified from proteomic studies will help us to further understand the mechanisms of abiotic stress resistance in P. patens.